Risk Factors of Carbohydrate Consumption among Adult Women In Indonesia - Daus, Firdaus Firdaus; Rimbawan, Rimbawan; Briawan, Dodik (Jurnal Nutrire Diaita (Ilmu Gizi), 2020)
The aims of study were to analyze risk factors of carbohydrate consumption among adult women aged 19-49 years in Indonesia such as Body Mass Indexs (BMI), ages, education level, tipe of occupation, house hold income and urban-rural settlement. The study used data of the Basic Health Research (Riskesdas) 2010 of the Health Reseach and Development Agency of the Ministry of Helath, which was designed as a cross sectional survey. Total sample woman age 19-49 years was 52044 were selected for analysis. A multiple logistic regression model was applied to analyze the risk factors. The prevalence of consumption carbohidrate below 60% of energy adequancy from carbohydrate among woman was 31,6%. The results showed that the significant risk factor of carbohydrate consumption among adult woman were education level (OR for low education= 0.830, CI: 0.776-0.887), household income (OR for low income= 0.905, CI: 0.870-0.942) and urban-rural settlement (OR for rural= 0.564, CI: 0.542-0.587). Normal BMI, high education level, woman with occupation, high household income and urban settlement are protective factors for carbohydrate consumption.Â